THE UNCOMFORTABLE KUHN. A REVOLUTIONARY READING OF DISBELONGING: TO WHAT DOMAIN SHOULD WE LEAVE THE KUHNIAN INHERITANCE? K. BRADY WRAY, 2021, Kuhn’s Intellectual Path. Charting “The Structure of Scientific Revolutions”, Cambridge, Cambridge University Press, ISBN-10: 1316512177, ISBN-13: 978-1316512173 (Annals of the University of Bucharest. Philosophy Series, 2024)
About Kuhn we have already read, in 60 years since the release of the Structure of Scientific Revolutions, critiques portraying him as a transgressor, a visionary, a reformist of the history and philosophy of science. But to achieve all this capital of notoriety and to raise a tradition by itself – for which many turned the partisanship for his convictions into a title of nobility, becoming “Kuhnians” – having a touch of genius is not enough: one’s education is as important as one’s innate talent. Understanding Kuhn’s Intellectual Path is not only a curiosity, but also an exotic epistemic travel to different philosophical openings of his education, which influenced – contingently or decisively – his unique theory on the change of paradigms in the history of science. K. Brad Wray offers us intriguing insights on Kuhn’s intellectual becoming in one of his recent volumes published by Cambridge University Press (2021).